Measuring shared decision making in oncology: Development and first testing of the iSHAREpatient and iSHAREphysician questionnaires - Hanna Bomhof‐Roordink; Fania R. Gärtner; Nanny vanDuijn‐Bakker; Trudy van derWeijden; Anne M. Stiggelbout; Arwen H. Pieterse (Wiley, 2020)
Abstract Background Existing measures to assess shared decision making (SDM) have often been developed based on an ill‐defined underlying construct, and many assess physician behaviours only or focus on a single patient‐physician encounter. Objective To (a) develop a patient and a physician questionnaire to measure SDM in oncology and (b) determine their content validity and comprehensibility. Methods A systematic review of SDM models and an oncology‐specific SDM model informed the domains of the SDM construct. We formulated items for each SDM domain. Cancer patients and physicians rated content validity in an online questionnaire. We assumed a formative measurement model and performed online field‐testing in cancer patients to inform further item reduction. We tested item comprehension in cognitive interviews with cancer patients and physicians. Results We identified 17 domains and formulated 132 items. Twelve cancer patients rated content validity at item level, and 11 physicians rated content validity at domain level. We field‐tested the items among 131 cancer patients and conducted cognitive interviews with eight patients and five physicians. These phases resulted in the 15‐item iSHAREpatient and 15‐item iSHAREphysician questionnaires, covering 13 domains. Conclusions We thoroughly developed the iSHARE questionnaires. They both assess patient and physician behaviours and cover the entire SDM process rather than a single consultation.